Pembelajaran Lompat Tinggi Melalui Pendekatan Permainan Empat Pos (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This study aims to improve the learning style straddle high jump with a four-post game approach in the fourth-grade students of SD Negeri 01 Sub Lebaksiu Lebaksiu Kidul Regency Tegal 2014. The method of this study is Classroom Action Research (CAR). This study uses two cycles where each cycle consists of 1) Planning; 2) Implementation of the action; 3) Observation; 4) Reflection. In addition to the observations made during the process of learning and research activities take place in the form of a questionnaire developed questionnaires learning interest questionnaire, to determine the extent of satisfaction and interest of students in the following study using the game. The results show that the learning outcomes using the High Jump with a four-game approach heading in fourth grade Lebaksiu State of South 01 Sub Lebaksiu Tegal positive impact. This can be seen in the results of students' mastery learning which exceeds the predetermined KKM 75 having mastery learning is mastery learning in the first cycle reaches 62.5%, while in the second cycle mastery learning reaches 90.63%. It can be concluded that the process of learning the high jump with a four-post game approach can improve student learning outcomes Lebaksiu Kidul fourth grade SDN Tegal 01 Sub Lebaksiu.